The effects of high repetition rate stimuli on electrocochleography performed on normal hearing subjects - Bowker, Caren Anne (My University, 2016)
High stimulus repetition rates have been proposed as a solution to the poor sensitivity and specificity of the standard electrocochleogram. The use of this approach has been confounded, however, by conflicting literature reports on the effects of high stimulus repetition rates on normal subjects. This study aimed to confirm the effects of high stimulus repetition rates on normal hearing subjects as a precursor to clinical high stimulus repetition rate electrocochleography trials. Electrocochleogram tracings were recorded binaurally from 51 normal hearing subjects at 7.1 cps, 51.1 cps, 101.1 cps and 151.1 cps and the summating potential and action potential latencies and amplitudes, summating potential/action potential amplitude ratios and waveform widths were recorded. Statistical analyses showed that increasing the stimulus repetition rate caused statistically (p<O.05) and clinically (p<O.O1 for latency and p<O.005 for amplitude) significant changes to the action potential latency and amplitude, summating potential/action potential amplitude ratio and waveform width, but caused only limited statistical (p<O.05) and clinical (p<O.OI for latency and p<O.005 for amplitude) changes to the summating potential amplitude and latency. Subject age had no effect on the results and there was no interaction between age and stimulus repetition rates. These findings provide the most comprehensive data on the effects of fast stimulus repetition rates to date, and have provided the beginnings of a valid clinical normative database for high stimulus repetition rate tympanic electrode electrocochleography.
THE DEPARTMENT OF SPEECH PATHOLOGY AND AUDIOLOGY. FACULTY OF ARTS, UNIVERSITY OF THE WITWATERSRAND, JOHANNESBURG In partial fulfillment of the requirements for the degree of Master of Arts by coursework in Audiology June 1999
Keywords: Ménière's disease.; Audiometry, Evoked response